Community Participation in Household Oil Waste Management as Environmental Mitigation Efforts: (Case Study in Gunung Anyar Tambak, Surabaya) - Syakira Mumtaz Sholehah; Aliza Dwi Kusuma Marsetyanti; Rizka Aprilia Nur Aini (Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines community participation in household oil waste management as an environmental mitigation effort in Gunung Anyar Tambak, Surabaya. The research aims to analyze community participation using Cohen and Uphoff’s theory and the 3R principle (reduce, reuse, recycle). This study uses a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. The findings show that community participation varies across four stages: decision-making, implementation, benefit-taking, and evaluation. Participation is relatively high in implementation but low in decision-making and evaluation stages. The program provides economic, social, and environmental benefits, although challenges remain in community awareness, infrastructure, and program management. The study concludes that stronger stakeholder collaboration and participatory governance are needed to enhance sustainable waste management practices.